Safe and sustainable plasmapheresis. (3rd October 2017) - Pink, J.; Bell, B.; Kotsiou, G.; Wright, S.; Thyer, J.
Abstract : Background and Objectives: Our aim is to present the recent Australian experience in trying to optimise collections from our apheresis program to meet the challenge of increasing demand for intravenous immunoglobulin. This is against a background of decreasing red cell demand, resulting in less recovered plasma from whole blood. Materials and Methods: We extracted data from our donor and product databases and from targeted internal studies and audits. Data was analysed to determine the effects of donor factors, changes in collection processes and other interventions on the plasma volume, plasma quality, donor safety and donor return rates. Results: Vasovagal reactions remain a key adverse reaction in apheresis with implications not only for donor safety but also for donor return and therefore supply. Many factors influence reaction rates including donor selection and the details of the apheresis procedure. Other apheresis related complications include citrate reactions, iron deficiency and potentially bone health in long‐term donors. Changes in collection procedures can also affect product quality, which may negate benefits of increasing volume. Another key to maintaining supply is to optimise the frequency of donor visits, a major challenge in the non‐remunerated donor setting. Conclusion: In a time of increasing demand it is important to optimise immunoglobulin yield by retaining donors, increasing visit frequency and maximising volumes from each visit, whilst carefully balancing the risk of adverse reactions. Interventions must be assessed in terms of donor safety and also product yield. Both must be optimised if sustainability of plasma supply is to be achieved.